Are All Patients Going Home after Total Knee Arthroplasty? A Temporal Analysis of Discharge Trends and Predictors of Nonhome Discharge (2011–2020) - Pan, Xuankang; Xu, James; Rullán, Pedro J.; Pasqualini, Ignacio; Krebs, Viktor E.; Molloy, Robert M.; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2023)
Value-based orthopaedic surgery and reimbursement changes for total knee arthroplasty (TKA) are potential factors shaping arthroplasty practice nationwide. This study aimed to evaluate (1) trends in discharge disposition (home vs nonhome discharge), (2) episode-of-care outcomes for home and nonhome discharge cohorts, and (3) predictors of nonhome discharge among patients undergoing TKA from 2011 to 2020. The National Surgical Quality Improvement Program database was reviewed for all primary TKAs from 2011 to 2020. A total of 462,858 patients were identified and grouped into home discharge (n = 378,771) and nonhome discharge (n = 84,087) cohorts. The primary outcome was the annual rate of home/nonhome discharges. Secondary outcomes included trends in health care utilization parameters, readmissions, and complications. Multivariable logistic regression analyses were performed to evaluate factors associated with nonhome discharge. Overall, 82% were discharged home, and 18% were discharged to a nonhome facility. Home discharge rates increased from 65.5% in 2011 to 94% in 2020. Nonhome discharge rates decreased from 34.5% in 2011 to 6% in 2020. Thirty-day readmissions decreased from 3.2 to 2.4% for the home discharge cohort but increased from 5.6 to 6.1% for the nonhome discharge cohort. Female sex, Asian or Black race, Hispanic ethnicity, American Society of Anesthesiology (ASA) class > II, Charlson comorbidity index scores > 0, smoking, dependent functional status, and age > 60 years were associated with higher odds of nonhome discharge. Over the last decade, there has been a major shift to home discharge after TKA. Future work is needed to further assess if perioperative interventions may have a positive effect in decreasing adverse outcomes in nonhome discharge patients.
Keywords: knee arthroplasty; nationwide trends; discharge disposition; predictors; outcomes